Mobile APP prototype for Morehead State University - Ramírez-Hidalgo, Javier Ignacio (Instituto Tecnológico de Costa Rica, 2012)
The objective of this document is to explain and inform in a detailed way all the information regarding my capstone project at Morehead State University (MSU). The project consists in the development of a prototype of a prospective Morehead State University Mobile App. The process was divided into three main stages. The first stage was to develop a consistent problem and solution definition, a preliminary visual interface and architectural design and a technology ramp-up. The second stage consisted mainly in the development of the app itself and feedback gathering from students. Finally, during the third stage the information from the feedback gathering was used to improve the prototype and the app was showcased to Morehead State University’s directives.
Proyecto de graduación (Bachillerato en Ingeniería en Computación) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, 2012
Keywords: Aplicaciones móviles; Software; Teléfonos móviles; Redes sociales; Bases de datos; Administración de la información; Arquitectura de programas; Tesis